Analisa Dan Optimasi Produksi Sumur Migas Di PEP Bekasi - Hernowo Widodo; M. Samsuri; Samsul Ma’rif (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
Based on the results of the mass balance analysis and a review at PEP, it was concluded that the total feed intake from all wells was BOPD at 770 barrels/day, gas at 12.1882 MMSCFD, and BLPD at 15975.2 barrels/day, the total product produced was 8 ,541226% oil at 1568.760 barrels/day, 8.989134% condensate at 1651.027 barrels/day, 0.056535% gas at 10.3838214 MMSCFD, and 82.4131% water injection at 15136.748 barrels/day . In the Water Injection Plant process it produces sludge of 16286.812 kg or 0.90001% of the processed formation water, the formation of sludge is due to the addition of chemicals in the formation water treatment process.